VD_FINDINFO HC / 2016 / 350 vom 17. März 2016 - VD Tribunal cantonal (2016)
DROIT DE LA FAMILLE, MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, CALCUL, IMPÔT | 179 al. 1 CC, 312 al. 1 CPC (CH), 317 al. 1 CPC (CH)